EFFECTIVE PREPARATION OF UBE TEACHERS FOR SUCCESSFUL IMPLEMENTATION OF UBE PROGRAMME - Haliru, Umar; Zaki, Nafisa Abubakar (Sokoto Educational Review, 2020)
There is general outcry among Nigerians regarding the imbalance standard of education in the country. This will not be unconnected to the fact that the quality of teachers produced by the teacher training institutions in the country felt short of expectation. The quality of teachers in any given country is a reflection of the education system which produced them since the quality of the products of any educational system cannot be higher than that of the teachers charged with responsibility of facilitating learning among those who get exposed to that system. Teacher is therefore the most important factor in my educational undertaking. Government’s effort towards providing free and compulsory education is expressed through universal basic education (UBE) programme. The success of UBE programme is hindered by many factors some of which include insufficient and unqualified teaching staff at basic education, poor preparation of teachers who will teach at basic education, poor laboratories and libraries e.t.c. In view of this the paper highlighted the objective of universal basic education programme and identified some propitious strategies that will help in improving the quantity of teacher preparation programme. Finally the paper suggested, among other measures, the need to review the content of teacher preparation programme and continuous monitoring of UBE programme for possible adaptation.